Edukasi Perawat Kepada Pasien dan Keluarga Dalam Pencegahan Infeksi Pada Pasien Post Operasi di RSUD Dr. Soehadi Prijonegoro - Syerlita Eka Rahmawati; Tyas Dwi Rahayu; Zahra Diah Ayu Permatasari; Irma Mustika Sari; Wiji Lestari (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Post-operative is a condition after surgery and medical treatment to treat or repair damaged tissue or organs starting when the client is moved to the operating room and ending in the recovery room. Surgery is a medical procedure that uses invasive techniques by opening or displaying body tissue that will be treated through incisions and ending with wound suturing. This health education aims to improve the knowledge and skills of patients and families regarding the prevention of post-operative infections. This health education was conducted on Saturday, October 19, 2024 at 10:30 in the Teratai room using a material delivery method using leaflet media, demonstrating how to wash hands properly and wound care, and evaluating the results of the pre and post tests during the health education activities. After the health education activities were carried out, the results showed that the enthusiasm of the participants when participating in the health education activities was very high, seen from the material presentation session, the participants were seen paying attention to the material presented. During the activity, participants were active in asking questions and were able to answer questions and wanted to know more about the material that had been presented. The ability of participants in answering pretest and posttest questions also showed an increase because the audience when working on the pretest questions, an average of did not know the material to be presented with a total of 13 questions. Then, when working on the posttest questions, an average of had increased knowledge after the presentation of the material presented with the same number of questions. Early symptoms that appear when an infection occurs in a postoperative wound are open wounds/open stitches and there are signs of infection: Redness, Swelling, Pain, Decreased function of the infected organ, Pus, Fever. SSI is an infection that occurs in the wound area after surgery, surgical wound infections are divided into, internal, and organs. SSI is caused by various factors, namely the patient himself, health workers, the surgical process, the environment and surgical equipment. The correct hand washing process according to WHO includes wetting the hands, applying soap or hand sanitizer, rubbing the entire surface of the hands for at least 20 seconds, rinsing with water (if using soap), and drying the hands. 6-step hand washing is an effective hand washing method to remove germs, viruses, and bacteria from the hands. This step is designed to ensure that every part of the hand is properly cleaned.